Managing the monster in the mind: a psychoanalytically informed qualitative study exploring the experiences of people diagnosed with obsessive-compulsive disorder. Issue 2 (3rd April 2019) - Mulhall, K.; O'Connor, J.; Timulakova, K.
Abstract : The psychodynamics of Obsessive-Compulsive Disorder (OCD) have received only sporadic and passing attention in recent decades; at the same time, psychodynamic approaches are specifically discouraged as a treatment within the mainstream guidance to mental health clinicians. Despite only mild evidence of meaningful change along this line, with a high level of continued difficulties noted and a high level of non-participation too, current research and treatment recommendations for OCD centres on a biological and cognitive and/or behavioural models and interventions. This study sought to examine the experiences of individuals living with OCD, including an exploration of early life experiences and interpersonal patterns. Five men and one woman were interviewed on three occasions using the psychoanalytically informed research interview. Three core themes emerged very strongly: firstly, participants' struggles to handle parental turmoil ('Handling parental turmoil'); secondly, withstanding parental criticism ('Enduring criticism'); and lastly, the sense of expression as something forbidden ('Struggling with emotional expression'). This study located interpersonal experiences within participants' accounts that appeared to connect with the origins and development of their obsessions and compulsions. The role that relationally oriented approaches may have for people presenting with these difficulties are also discussed.